Identification of short-length oligonucleotides biomarker for canine species detection using mitochondrial cytochrome b gene - Rahman, Md. Mahfujur; Ali, Md. Eaqub; Bhassu, Subha; Abd Hamid, Sharifah Bee; Mustafa, Shuhaimi (Elsevier, 2014)
Introduction: Stray dogs are still available in certain countries without any offered price and made it as a potential source for adulteration with costly meats for more benefit. Furthermore, human forensic evidences from crime scenes were often integrated with biomaterial of canine origin. Most of the DNA based assay for canine species detection used longer amplicon size (>150 bp) which are not suitable for highly degraded food or forensic sample analysis. Therefore, in this study for development of short length canine specific biomarker, mitochondrial cytochrome b (cytb) gene was targeted using simple PCR assay.